FAKTOR YANG MEMPENGARUHI PENGEMBALIAN ADMINISTRASI KLAIM BPJS KESEHATAN DITINJAU DARI SYARAT-SYARAT KELENGKAPAN ADMINISTRASI KLAIM - Mustika Kurniawati (CHMK HEALTH JOURNAL, 2020)
BPJS Health will make BPJS claim payments to the referral hospital requesting that the hospital have completed its obligation to request and complete the BPJS Health claims administration. Based on visit data in July 2018, Hospital X in Malang, which has been a provider of BPJS Health since 2014, is still discussing the administration of BPJS Health administrative claims by BPJS Health verifiers. Of the 882 BPJS claims administration files submitted, 31 (3.51%) files were issued, and most of them came from inpatient units, 26 (2.95%), while outpatient units were only available one fifth (1 / 5) of the total BPJS patient files. The purpose of this study is to study the root of the problem regarding the administration of BPJS claims. The design of this study used a descriptive research design, by means of Focus Group Discussion (DKT) with a team related to the completeness of the administration of BPJS claims, with a total of 6 people. The results obtained from the factors that affect the completeness of the administration of BPJS claims, namely the role of the casemix team and related units have not run optimally. This is due to the absence of a Hospital Regulation consisting of Casemix Guidelines, Guidelines and SPO, only a decree on the formation of the Casemix team. The hospital's problem solving made the Regulations consisting of Casemix Guidelines.Keywords: claims claims, Casemix, BPJS.